Biography and Action: A Schutzian Perspective to Life-world - Santos, Hermílio (SocietàMutamentoPolitica, 2016)
Starting with the discussion on free-will and action, this paper discusses how Alfred Schutz approaches these issues for the comprehension of life-world. After a brief overview on how contemporary philosophers as Ernst Tugendhat and Ulrich Pothast face these problem, it is argued that for Schutz action plays a central role in his conception of life-world. The article goes further and advocates for the importance of exploring individual biographies as a way to provide an accurate understanding of actions. By the end of this text, it is suggested that the biographical narrative approach, as proposed by Fritz Schütze, as well as by Gabriele Rosenthal, is an important contribution to the Schutz’ perspective of the life-world and to adequately explore the most different social phenomena.